Enhanced promotion of Ru-based ammonia catalysts by in situ dosing of Cs. Issue 8 (11th July 2022) - Shadravan, Vahid; Cao, Ang; Bukas, Vanessa J.; Grønborg, Mette K.; Damsgaard, Christian D.; Wang, Zhenbin; Kibsgaard, Jakob; Nørskov, Jens K.; Chorkendorff, Ib
Abstract : In situ dosing of metallic Cs on Ru surface results in a higher Cs coverage (compared to conventional ex situ promotion techniques) which enhances the catalytic performance of Ru for ammonia synthesis. Abstract : Ammonia synthesis via the high-temperature and -pressure Haber–Bosch (HB) process at large centralized facilities has a significant contribution to global CO2 emissions. Radically new catalysts should be discovered to enable sustainable ammonia synthesis processes that can operate at much lower temperatures to relax the demand for high pressure in the current HB process. In this manner, the capital requirement and energy consumption for making ammonia would decrease considerably and a de-centralized production could become feasible. Herein, we present a new class of ruthenium-based catalysts promoted with metallic cesium using an in situ preparation technique. The catalysts prepared with this new technique showed up to a factor of ∼10 higher activity compared to the ones prepared by traditional ex situ promotion methods. The in situ promoted catalyst also has a smaller apparent activation energy and is less susceptible to H2 poisoning. We systematically investigate the promotional role of in situ dosed Cs and propose a detailed model supported by extensive density functional theory calculations to explain the difference between the promotional effect of the in situ and traditionally ex situ prepared catalysts.